The Influence Of Purchasing And Distribution Of Goods On The Store Inventory Of The Accouting Department At Surya Hotel - Utami, Yuli Dwi; Mustika, Dama (Jurnal Ekonomi, 2024)
This research aims to provide an overview of the role of purchasing and distribution in Surya Hotel inventory. In this research the author discusses three (3) main issues, namely what is the role of purchasing goods in the accounting department supply shop at Surya Hotel, what is the role of distribution of goods in the accounting department supply shop in Surya, and what is the role of goods distribution in the accounting department supply shop in Surya. the role of purchasing and distributing goods in the inventory shop accounting section at Surya Surya Hotel.The research method used is a qualitative method. The technique used is to conduct interviews with accounting staff such as cost control, purchasing and storekeeper at Surya Hotel as well as making direct observations regarding the role of purchasing and distributing goods in the inventory store of the accounting department at Surya Hotel.From the results of this research discussion, it can be concluded that purchasing goods plays a very important role in the Surya Hotel store inventory. Goods that have arrived will be input by the storekeeper in the application (Inventory control) and will automatically add inventory/stock in the system owned by the hotel accounting. Distribution of goods plays a role in Surya store inventory. Hotel goods distribution is the movement of goods from the store to other departments. Some of these roles are, reducing the amount of inventory/stock/inventory in the accounting system, increasing the amount of inventory/stock/inventory in the user's system (another department), and making it a cost for the user (another department).